2013
DOI: 10.1016/j.ijrobp.2013.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Cardiac Mortality After Hypofractionated Radiation Therapy in Breast Cancer

Abstract: The degree of hypofractionation and parasternal photon beams contributed to increased cardiac mortality in this patient cohort. Differences emerged after 12 to 15 years, indicating the need of more studies with observation time of 2 decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 126 publications
(163 reference statements)
0
19
0
1
Order By: Relevance
“…The authors concluded that at least two decades is needed to evaluate safety of such irradiation [13].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that at least two decades is needed to evaluate safety of such irradiation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Tjessem et al investigated hypofractionated radiation therapy in breast cancer patients who received either 10 fractions of 4.3 Gy 32/week (43 Gy total dose) or 20 fractions of 2.5 Gy 35/week (50 Gy total dose). They found patients who received a lower total dose, but higher dose per fraction, had an increased risk of developing fatal ischemic heart disease compared to the group with lower dose fractions (49). This suggested that even if the total dose is lower, a higher dose per fraction was more harmful than a lower dose per fraction with a higher total dose.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Hypofractionation (HF) is currently not recommended for patients who receive RNI, as larger doses per fraction may increase the risk of long-term effects such as cardiac toxicity or plexopathy [36,37,38]. In the randomized studies investigating HF, 79% of the patients were node negative, only a minority of patients were treated with RNI (Canadian study: none, START A trial: 13%, START B trial: 7% [39,40]).…”
Section: Targeting Technique and Dose For Rnimentioning
confidence: 99%